Sarason’s Conjecture of Toeplitz Operators on Fock-Sobolev Type Spaces - Xiaofeng Wang; Jianjun Chen; Jin Xia (Journal of Function Spaces)
In this note, we will solve Sarason’s conjecture on the Fock-Sobolev type spaces and give a well solution that if Toeplitz product TuTv¯, with entire symbols u and v, is bounded if and only if u=eq, v=Ce-q, where q is a linear complex polynomial and C is a nonzero constant.